Testosterone Replacement Protects Against Non-Alcoholic Fatty Liver Disease in Castrated Male Mice - Liqaa Oday Ali (Journal of Global Pharma Technology, 2018)
The present work aimed to study histopathological, histochemical and biochemical changes in the liver of castrated male mice and effect of possible treatment with testosterone. For this purpose Forty five (45) male albino mice (3weeks) aged were divided into 3 groups (n = 15).The Group I was used as a control, Group II was castrated group, Group III was castrated treated with testosterone group .For 6 weeks from period February to June 2017, lipid profile was measured. There are significant p increased in (cholesterol, triglycerides, and low density lipoprotein LDL) levels, but there is no change in the level of HDL   in the castrated group as compared with the control group. In addition, histopathological changes of the liver were examined. Castration enhanced lipid accumulation liver (macrovesicular steatosis), ballooning degeneration in hepatocytes all these changes associated with inflammatory cellular infiltration. Histochemically accumulation of lipid in hepatocytes were strongly positive to Sudan Black B reaction in liver of castrated mice as compared with the control group and these structural changes were less pronounced in animals treated with testosterone. From the present results, it can be concluded that testosterone replacement ameliorates role in non alcoholic fatty liver disease. Keywords: Non-alcoholic fatty liver disease, Testosterone, mice, steatohepatitis, hepativ lipid accumulation.